If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -3) + 2x = 10 Reorder the terms: 4(-3 + x) + 2x = 10 (-3 * 4 + x * 4) + 2x = 10 (-12 + 4x) + 2x = 10 Combine like terms: 4x + 2x = 6x -12 + 6x = 10 Solving -12 + 6x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 6x = 10 + 12 Combine like terms: -12 + 12 = 0 0 + 6x = 10 + 12 6x = 10 + 12 Combine like terms: 10 + 12 = 22 6x = 22 Divide each side by '6'. x = 3.666666667 Simplifying x = 3.666666667
| 1+15=-4(4x-4) | | 7x+9y=3+9x | | 30x^2+273x-270=0 | | m+11/8=8 | | 1+15=4(4x-4) | | 15x-5=25x+3 | | 2(x-3)+10=18 | | -4(x+1)-14=16+2 | | x+7+4x-3=3x+x-2x+16 | | 5k-3/(-3) | | y=-(1/3)x | | y=7000x+b | | 5k-3/3 | | 5k-3/-33 | | y=7000x | | 2(3x+9)=29+35 | | 4b^3(2b^4-10b^3+3)= | | 10z-7=6 | | 7/2(2/3-5/4x)=3/10 | | 5y-6y=5 | | 9z-z=-2+4z-2-4 | | 16x+24=8 | | 3x+7=9x+19 | | 8w^8*3x^6w^3*2x= | | -3(3p+5)-2(2-11p)=3(1+4p) | | -5x+6x=4-8 | | -3(-6y+6)-8y=4(y-6)-2 | | 8w^8*3x^6*w^3*2x= | | sin(6x)+sin(12x)=0 | | 5+ln(x+3)=4 | | 5/d=-6 | | -4-8=2x+2x |